2013
DOI: 10.1111/aec.12049
|View full text |Cite
|
Sign up to set email alerts
|

Are invasive species drivers of native species decline or passengers of habitat modification? A case study of the impact of the common myna (Acridotheres tristis) on Australian bird species

Abstract: Habitat modification and invasive species are significant drivers of biodiversity decline. However, distinguishing between the impacts of these two drivers on native species can be difficult. For example, habitat modification may reduce native species abundance, while an invasive species may take advantage of the new environment. This scenario has been described as the driver‐passenger model, with ‘passengers’ taking advantage of habitat modification and ‘drivers’ causing native species decline. Therefore, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 49 publications
1
28
0
1
Order By: Relevance
“…Evidence is accumulating that in many geographical locations, opportunism and flexibility are key to its ecological success, rather than any competitive ability (Grarock et al, 2013;Lowe et al, 2011;Parsons et al, 2006;Shirley & Kark, 2009;Sol, Bartomeus, et al, 2012a). Noisy miners are also extremely abundant, but the success of the species is probably underpinned by the overabundance of certain types of vegetation in back gardens coupled with their highly effective aggressive exclusion of other avian species from these resources (Parsons et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is accumulating that in many geographical locations, opportunism and flexibility are key to its ecological success, rather than any competitive ability (Grarock et al, 2013;Lowe et al, 2011;Parsons et al, 2006;Shirley & Kark, 2009;Sol, Bartomeus, et al, 2012a). Noisy miners are also extremely abundant, but the success of the species is probably underpinned by the overabundance of certain types of vegetation in back gardens coupled with their highly effective aggressive exclusion of other avian species from these resources (Parsons et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One of only three bird species to be listed in the top '100 World's Worst Invasive Alien species' by the International Union for the Conservation of Nature (IUCN), Australian public opinion considers it the most significant pest (http://www.abc.net.au/tv/wildwatch/results/award.htm) and it is the target of ongoing pest control measures. Although the species has been reported to aggressively defend its nest (Pell & Tidemann, 1997), it is becoming increasingly clear that it owes much of its ecological success to its opportunistic nature that allows it to occupy niches that most natives are unable to invade owing to their greater dependence upon natural habitats for breeding (Grarock, Tidemann, Wood, & Lindenmayer, 2013;Lowe et al, 2011;Parsons et al, 2006;Sol, Bartomeus, et al, 2012a). Several recent studies have shown that it is most often the recipient of aggression around food sources and it is no more aggressive than would be expected on the basis of its occurrence (Haythorpe, Burke, & Sulikowski, 2013;Lowe et al, 2011;Sol, Bartomeus, et al, 2012a).…”
mentioning
confidence: 99%
“…This may further exacerbate the deleterious influence of roads for a number of nearby populations through the establishment of highly competitive edge specialist species capable of utilizing the new resources provisioned by roads (Grarock et al, 2014;Morelli et al, 2014). For example, a number of highly aggressive species, including the noisy miner (Manorina melanocephala), blue-faced honeyeater (Entomyzon cyanotis) and noisy friarbird (Philemon corniculatus), were regularly observed at a number of more highly disturbed sites in the current study (personal observation).…”
Section: Habitat Augmentationmentioning
confidence: 99%
“…Insects and arachnids may be noteworthy exceptions in this regard, however, as Gao and Reitz (2017) review many examples of competitive displacement (p. 166: "elimination of one species by another with the same ecological niche"). But in many cases, the role of invasive species in driving native species to low numbers is unclear, as competition and other species interactions are often confounded with other major factors impinging simultaneously on native species, such as habitat modification and loss (e.g., Wilcove et al, 1998;Gurevitch and Padilla, 2004;Didham et al, 2007;Berman et al, 2013;Grabock et al, 2014;Honek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%